Total synthesis and structural revision of stagonolide D - Vadhadiya, Paresh M.; Puranik, Vedavati G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2012)
The total synthesis of the putative structure of stagonolide D has been completed. The relative and absolute configuration of stagonolide D was established by synthesizing its optical antipode. The adopted strategy involves the construction of the central macrolide employing ring-closing metathesis (RCM), followed by selective protecting group manipulations and a final concomitant −OTBS deprotection and displacement of an −OMs placed next to it, resulting in the formation of the epoxide ring.

Total synthesis of mangiferaelactone - Vadhadiya, Paresh M.; Ramana, C. V. (Tetrahedron Letters, 2014)
Herein we document the first total synthesis of mangiferaelactone and thus establish its absolute configuration. The central nonenolide ring was constructed using ring closing metathesis and Yamaguchi esterification. The key alcohol fragment was synthesized by the Bernet-Vasella fragmentation of C-ribofuranoside. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Bernet-Vasella fragmentation; Nonenolide; Ring closing metathesis; Total synthesis; Yamaguchi protocol

Studies toward the total synthesis of cytospolide E - Vadhadiya, Paresh M.; Rout, Jeetendra K.; Ramana, C. V. (Tetrahedron, 2015)
In this manuscript, we describe various approaches that we have examined towards the total synthesis of Cytospolide E. We initially attempted the RCM approach employing first and second generation Grubbs and Grubbs-Hoyeda catalysts resulting in the exclusive synthesis of the Z-isomer of Cytospolide E. With the Furstner catalyst, the dimerization involving the less hindered olefin was the exclusive event. Alternative approach documented is a successful cross-metathesis leading to a seco-acid with the requisite E-configuration and undesired macrodiolide formation during the attempted Shiina's lactonization. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: 20-Membered macrodiolide; Nonenolide; Ring closing metathesis; Shiina lactonization; Yamaguchi esterification

Total synthesis of sinenside A - Vadhadiya, Paresh M.; Ramana, Chepuri V. (Organic Letters, 2015)
The first total synthesis of norlignan glucoside sinenside A has been accomplished. An intramolecular acetalization reaction has been employed as the key skeletal construct to forge the central cyclic disaccharide core. The trans-1,2-diol configuration present in the cyclic disaccharide of this natural product is unique and has been addressed by setting this configuration at the beginning. A 1,2-orthoester group has been selected as a handle for both sp glycosidation and for differentiation of the C2'-OH (that participates in the key acetalization reaction) of the sugar unit.